Use of Laringeal Mask Airway during General Anaesthesia in Ambulatory Surgery - Hospital Nacional Guillermo Almenara I. Mayo 1995 - Enero 1999 - Castañeda Kcomt, José (1999)
OBJECTIVE: To describe the Laryngeal Mask Airway (LMA) employment in our Department of Ambulatory Surgery with regards to size selection, employment criteria, and related surgical procedures. MATERIALS AND METHODS: 2443 patients, with the ages between 4 months and 91 years, underwent LMA from May 1991 to January 1999. We describe patient selection, carefulness, LMA sizeelection criteria, anaesthetic approach and level of successful insertion in the first two attempts. RESULTS: LMA size 1 was used in infants; size 2 for patients 1-6 years of age (and girls up to his fifties); size 3 for women older than 15 years of age, and for men 12-20 years of age; and size 4 and 5 for adult males, regarding their physical nature. LMA insertion was achieved at first attempt in 2199 (90,02%) patients, and second attempt in 244 (9,98%) patients. In 14 patients LMA intubing was unsuccessful. CONCLUSION: LMA is dramatically important for the development of ambulatory surgery anesthesia, and the size selection based on patient age is a safe choice.